Comparing PD-L1 with PD-1 antibodies combined with lenvatinib and hepatic arterial infusion chemotherapy for unresectable hepatocellular carcinoma - Li, Shaohua; Mei, Jie; Zhao, Rongce; Zhou, Jing; Wang, Qiaoxuan; Lu, Lianghe; Li, Jibin; Zheng, Lie; Wei, Wei; Guo, Rongping (Frontiers in Immunology, 2024)
A combination of hepatic arterial infusion chemotherapy (HAIC), lenvatinib, and immune checkpoint inhibitors (ICIs) yields a high tumor response rate and survival benefit in unresectable hepatocellular carcinoma (uHCC). However, the selection criteria for different ICIs remain unclear. This study aims to compare the efficacy and safety of PD-1/PD-L1 antibodies combined with HAIC and lenvatinib.HAIC+lenvatinib+PD-1/PD-L1 antibody from June 2019 to January 2022. We utilized propensity score matching (PSM) to select and match 60 patients treated with HAIC + durvalumab + lenvatinib (HDL) against 60 patients treated with HAIC + PD-1 antibodies + lenvatinib (HPL) to compare the efficacy and safety profiles of these two groups.After PSM, the baseline characteristics were well-balanced between the HDL and HPL groups. The overall survival (p = 0.293) and progression-free survival (p = 0.146) showed no significant difference. The objective response rate (ORR) was higher in the HDL group compared to the HPL group according to modified RECIST (74.1% vs. 53.6%, p = 0.022) and RECIST 1.1 (60.3% vs. 41.1%, p = 0.040), respectively. The incidence of grade 3 or 4 adverse events (AEs) was 10.0% and 18.3% (p = 0.191) in the HDL and HPL groups, respectively.PD-L1 antibody appears to be a preferable companion in the combination therapy of HAIC + ICIs + lenvatinib compared to PD-1 antibody, showing higher ORR and relatively lower incidence of severe AEs. Further prospective studies involving a larger patient population are warranted.